Strategies for Engaging and Communicating with Elected Officials - Ricky W. Telg; Shelli D. Rampold (EDIS, 2018)
This EDIS document is part of a series on communicating with elected officials.  This publication details a strategy for those who are seeking to engage and communicate with elected officials.